Kemampuan Kinerja Keuangan Untuk Meningkatkan Daya Saing UKM Yang Berbasis Green Economy - Sriyono Sriyono (Journal Competency of Business, 2018)
The majority of SMEs in its activities is how to obtain the highest possible profits without pay attention to the potential negative impacts. The purpose of this research is how to increase the financial performan through strengthening the financial performance through the strengthening of institutional and production on the SME-based green economy.. The methodology used in this study by doing observation as well as administering the questionnaire to SMEs, then the results of these questionnaires do tabulate and analyzed using the structure equation model and then do analysis by AMOS. Based on statistical analysis of the results obtained that financial performan has no capability as full variable intervening to the financial performan and competitivness on SMES based on green economy